Determination of spatial distribution, dissipation, and efficacy of insecticides used for control of citrus greening disease - Rehberg, Rachelle Anne, author; Borch, Thomas, advisor; Henry, Chuck, committee member; Bailey, Travis, committee member; Trivedi, Pankaj, committee member (Colorado State University. Libraries, 2022)
Citrus greening disease has devastated citrus production globally. While Florida growers explore management strategies, Asian citrus psyllids (ACP) continue spreading this detrimental disease. Determining the efficacy of insecticides applied in citrus groves is a necessity. In these field studies, the efficacies of foliar insecticide treatments to citrus trees were investigated with liquid chromatography tandem mass spectrometry. Insecticide spatial distribution, dissipation, degradation, and effectiveness at reducing ACP were quantified over time after commercial application at a field site in Florida. Citrus leaves, and sample discs attached to leaves, were collected at specific times and locations within individual citrus trees. ACP were inspected before and after treatments to quantify reductions associated with insecticide concentrations over time. We investigated several insecticides commonly used against ACP including malathion, imidacloprid, dimethoate, and one newer insecticide, afidopyropen. Our findings showed highly variable spatial distribution of insecticides throughout individual trees and rapid dissipation within 24 hours after application. Inadequate distribution to different sides of the leaf and tree canopy areas was observed for all aerial and ground spraying methods tested. Fast degradation rates were observed in sampling discs and citrus leaves with half-lives ranging from 0.6 to 4.0 hours while metabolite concentrations increased. Results showed faster dissipation rates during warmer months (July) and in younger-aged trees ground sprayed with the speed-sprayer. A wide range of insecticide efficacy was observed, with ACP reductions of 63 to 100%. When ACP remained after treatment, effectiveness decreased over time and ACP increased (e.g. from 6 to 172% after afidopyropen treatment). The observed variable spatial distribution, rapid insecticide dissipation, and inadequate efficacy allow remaining ACP or ACP from surrounding groves to continue spreading citrus greening disease, leaving citrus trees unprotected. For contact, or semi-systemic insecticides like afidopyropen, full coverage to both sides of the leaves and tree canopy is crucial to effectively manage ACP populations. ACP regeneration suggests lower metabolite toxicity or pest resistance development and reveals ineffective pest management. This research not only helps inform citrus growers of actual insecticide efficacy in the field, which may influence their pest and disease management strategies, but also provides better understanding of insecticide dissipation from citrus leaves, which assists those advancing predictive models for agricultural applications. Additionally, these results help inform insecticide manufacturers of their products' performance in field conditions which can be compared to laboratory studies. Lastly, this work reveals information on the fate of insecticides in the field which could be used to evaluate its impact on other species and the environment.
Keywords: citrus greening; Huanglongbing; pesticide dissipation; disease management; Asian citrus psyllid; pest management